Initial findings suggest box jellyfish encounters along shallow Philippine coastlines are predictable - Licuanan, Wilfredo Y.; Verdadero, Francis Xavier D.; Ang, Julia Louise; de los Santos, Berlin Jr.; Metillo, Ephrime B. (2021)
Jellyfish stings account for numerous deaths in the Philippines. Despite this, there is little scientific information on the identity, distribution, seasonality, and ecology of the box jellyfish species involved. We present initial findings of three months (April-June 2021) of monitoring the abundance of and envenomations by box jellyfishes in eastern and western Luzon. -Title page.
Includes bibliographical references.
Keywords: Jellyfishes -- Luzon (Philippines).; Cubomedusae -- Luzon (Philippines).